VARIATION OF THE ANATOMIC CHARACTERISTICS OF Anthocleista grandiflora WOOD AS A FUNCTION OF TREE AGE AND TRUNK POSITION (Nativa, 2024)
ABSTRACT: This paper presents significant findings on the variation in the anatomical properties of Anthocleista grandiflora wood, which could greatly influence its utilization in various products. Cubic-shaped heartwood and sapwood specimens were extracted at the base, middle, and top of boles from 38-, 43-, and 47-year-old trees. The variations in cell morphology and anatomical characteristics were meticulously assessed. The specimens were prepared into 3 mm x 10 mm fragments, macerated, and viewed under a microscope using Motic Image plus 2.0 ML software. The following parameters were determined: average values of fiber length, fiber diameter, lumen width, double fiber wall thickness, Runkel ratio, aspect ratio, coefficient of rigidity, and coefficient of flexibility of trees at the base, middle, and top. Notably, there were more vessels in sapwood than in heartwood, and the vessel areas increased with increasing vessel lengths. The results also revealed that in the heartwood region, the fraction of vessel lumen increases with tree age in the base, middle, and top sections. These findings are significant as they provide a comprehensive understanding of the anatomical properties of A. grandiflora wood, which is classified as wood from numerous vessels, a common characteristic of noble woods. The wood exhibited anatomical properties suitable for cellulose, paper, and fiber-based products, highlighting its potential in various industries.Keywords: wood quality; fibers; morphological characterization; timber industry. Variação das características anatômicas da madeira de Anthocleista grandiflora em função da idade e da posição no troco RESUMO: Objetivou-se avaliar as propriedades anatômicas da madeira de Anthocleista grandiflora e as suas possíveis aplicações. Amostras do cerne e alburno foram extraídas na base, meio e topo de árvores com 38, 43 e 47 anos de idade. Em seguida, foram avaliadas variações na morfologia celular e nas características anatômicas, por meio de fragmentos de 3 mm x 10 mm, macerados e visualizados em microscópio utilizando o software Motic Image plus 2.0 ML. Foram avaliados: comprimento da fibra, diâmetro da fibra, largura do lúmen, espessura da parede dupla da fibra, razão de Runkel, razão de aspecto, coeficiente de rigidez e coeficiente de flexibilidade das árvores na base, meio e topo. Verificou-se mais vasos no alburno do que no cerne, e as áreas dos vasos aumentaram com o aumento de seu comprimento. Os resultados obtidos também indicaram que na região do cerne a fração do lúmen dos vasos aumenta com a idade árvores nas seções da base, intermediária e topo, sendo os valores de 14.76, 11.38 e 20.73 mm para 38 anos; 23.74, 22.13 e 23.09 mm para 43 anos; 28.62, 12.89 e 25.01 mm para 47 anos. A A. grandiflora foi classificada como madeira de numerosos vasos, característica comum para madeiras nobres. A madeira apresentou propriedades anatômicas adequadas para celulose, papel e produtos à base de fibras.Palavras-chave: qualidade da madeira; fibras; caracterização morfológica; indústria madeireira.